Spomin na otroštvo pesnika Andreja Brvarja - Švajncer, Marija (Otrok in knjiga, 1992)
In the article an artistic and literary remember of childhood by poet Andrej Brvar is analysed. He has written some excellent poems for children, and a great number of poems for adults. He has written mostly in free verse. He became recognised as an important Slovene poet.
Keywords: Brvar, Andrej, 1945-; Slovene literature; slovenska književnost; poezija; slovenski pesniki; literarne študije